(untitled) (Journal of Parents and Teachers, 2014)
The article presents a didactic proposal to work on effects and feelings based on the film Belle Époque. In this way, the authors detail in a very precise way the contents, objectives and activities that make up the intervention so that other teachers are able to take it to the classroom. The evaluation of the proposal is also included, which shows its effectiveness and potential in the classroom.